Artificial Intelligence (Ai) Application In Islamic Finance: A Review Of Business Use Cases - Othman bin Abdullah; Mohd Shukor bin Harun; Amir Shaharuddin; Muhamad Azhari Wahid (Penerbit USIM, 2024)
This paper aims to review the use cases of AI applications implemented in Islamic financial institutions across the globe to get some understanding on how AI can be applied in real business environment of providing Shariah compliant financial services. To get real industry examples, the study utilizes content analysis method in reviewing Islamic financial technology reports and related news. The findings indicate that Islamic financial institutions across the globe have incorporated AI based digital innovations in general operations. However, AI applications in the Shariah compliance aspect is still limited. A more coordinated collaboration among academics and Islamic finance industry players with respective Shariah and technology backgrounds is crucial to unleash the potential of AI applications in Shariah compliance of Islamic finance.